Economic territory system socialisation as society development factor - R. M. Sadykov; V. Yu. Akhmetov (Вестник университета)
The economy socialisation problem and its impact on the social and economic territorial systems’ development is relevant and relatively new in contemporary conditions. However, the content of this phenomenon still is poorly studied and insufficiently adapted to social development at national and regional levels. The purpose of the study is to reveal the socialisation essence of the economic territory system as a factor in the social development and to define priority areas for humanisation of this system. To achieve this purpose, the following tasks solved: first, the content of the phenomenon, reflected in the economy socialisation concept, analysed, and its most successful interpretations established in domestic social science, designated, secondly, the main characteristics of the territories social development determined and described in details: social orientation and responsibility of the economy, property socialisation and needs, labour humanisation and mitigation of social differentiation, human and social capital development. The article contains recommendations for changing the role and income structure of employees and improving labour protection and safety, which can further ensure the economy socialisation. The results of the study expand knowledge about the development potential of territorial economic systems and society.